A two-step, one pot preparation of amines via acyl succinimides. Synthesis of the calcimimetic agents cinacalcet, NPS R-467, and NPS R-568. Issue 30 (22nd July 2015) - Gooodman, Cassie A.; Janci, Elise Marie; Onwodi, Olivia; Simpson, Chad C.; Hamaker, Christopher G.; Hitchcock, Shawn R.
Graphical abstract: Abstract: A method has been developed for the preparation of amines through a process of coupling acyl succinimides derived from commercially available carboxylic acids with amines to afford the corresponding amides. These amides are then reduced in situ with either diisobutylaluminum hydride or lithium aluminum hydride. The reaction tandem of the coupling reaction followed by the reduction affords the amine in fair to good yields after purification by flash chromatography. This one-pot, two reaction tandem process has been successfully applied to the synthesis of the calcimimetic agents cinacalcet, NPS R-467, and NPS R-568.